Estimation of ricin in castor varieties and hybrids by Lowry method: Estimation of ricin in castor varieties and hybrids by Lowry method - P ARUTCHENTHIL; S R VENKATACHALAM; S MANICKAM; V RAVICHANDAN; P A SARAVANAN; P VEERAMANI (Journal of Oilseeds Research, 2023)
Development of castor cultivars with reduced levels of ricin would improve the economics of castor oil production, reduce the potential for accidental poisoning and eliminate the potential of ricin. The presence of ricin in the high protein meal of castor remaining after oil extraction has historically reduced its value as an animal feed.Castor meal when applied as an amendment to greenhouse potting media suppress root-knot nematode. Ricin has historically been degraded by exposure to high temperature for two or more hours.